Ertel potential vorticity versus Bernoulli streamfunction on Mars. (13th November 2016) - Dowling, T. E.; Bradley, M. E.; Du, J.; Lewis, S. R.; Read, P. L.
Abstract : Scatter plots of Ertel potential vorticity, Q, versus Bernoulli streamfunction, B, on potential temperature surfaces, θ, are investigated for Mars using the global Mars Analysis Correction Data Assimilation (MACDA) reanalysis, which spans Mars Year (MY) 24.39 to 27.24. In midlatitudes, Mars exhibits monotonic, function‐like Q ( B ) correlations on θ surfaces similar to those observed for Earth. We quantify this with linear regressions of Q versus B over the vertical range θ =400 to 900 K (∼30 to 60 km). In autumn, winter and spring, in both hemispheres, the non‐dimensionalized correlation generally lies between zero and unity and gradually decreases with height, whereas in northern summer, it swings negative. These characteristics match Earth's lower mesosphere ( θ = 2000 to 3000 K; z ≈ 48 to 62 km) during the same seasons. The exception is southern summer, when the correlation on Mars nearly vanishes. In time series, the transition into and out of northern summer is sinuous and centred just after solar longitude L s = 90°, whereas in southern summer it is abrupt and spans ΔL s ≈120°, which is one third of a Mars year. A striking feature seen on Mars but not on Earth is a large range of Q over the narrow domain of B poleward of each winter polar jet, particularly in the north, which is consistent with the known annular structure of the Martian polar vortex. Froude number calculations suggest the existence of a planetary‐scale hydraulic jump associated with the winter polar jet. Abstract : The Figure shows the fastest jet stream on Mars, the northern‐winter polar jet, plotted in terms of Froude number, the buoyancy‐wave analogue of the Mach number, in Mars Year 26 at solar longitude 270 degrees. The data come from the Mars Analysis Correction Data Assimilation (MACDA), and are processed onto isentropic surfaces; shown is the 550 K potential temperature surface, near the core of the jet. Shooting (supercritical), streaming (subcritical) and critical regions are indicated in purple, brick‐red and white, respectively.